The impact of good governance on organizational health with the mediating role of organizational accountability: considering the influence of demographic and organizational variables - Taiebeh Taheri; Mohammad Amerzadeh; Ahad Alizadeh; Rohollah Kalhor (BMC Health Services Research)
Abstract Background Human resources are the critical element of organizations and serve as the economic engine of countries. Human resources play a crucial role in gaining competitive advantage. This study aimed to examine the impact of good governance on organizational health, with organizational accountability as a mediating factor, among employees of hospitals in Qazvin, Iran. Methods This analytical, applied research used a descriptive design and was conducted in selected hospitals in Qazvin in 2023. Data were collected from hospital staff who evaluated their hospitals’ organizational attributes, including good governance, organizational health, and accountability. Descriptive and inferential statistics were used to analyze the data. Standard questionnaires, including Singh and Jha’s (2018) Organizational Health, Moghimi and Ramazan’s (2011) Good Governance, and Jansen (2001) Organizational Accountability were used for data collection. To analyze the data and test the hypotheses, Pearson correlation coefficients were employed. Structural Equation Modeling (SEM) was employed for data analysis. Results The findings indicated that good governance directly affects organizational health and organizational accountability. Scores for good governance, organizational health, and organizational accountability in Qazvin hospitals were satisfactory. Good governance scores were higher among personnel with fixed shifts, contract staff, those with high school diplomas or lower education, educational groups and married personnel. Conclusion Based on the study results, hospital managers can enhance organizational health by improving governance and accountability. Further nationwide studies on the impact of organizational accountability on organizational health are recommended. To further advance the understanding of organizational health, future research should explore several key avenues.